Factors Affecting Length of Stay and Complications After Elective Anterior Cervical Discectomy and Fusion: A Study of 2164 Patients From The American College of Surgeons National Surgical Quality Improvement Project Database (ACS NSQIP). Issue 1 (February 2016) - Gruskay, Jordan A.; Fu, Michael; Basques, Bryce A.; Bohl, Daniel D.; Buerba, Rafael A.; Webb, Matthew L.; Grauer, Jonathan N.
Abstract : Study Design: Retrospective review of the prospective American College of Surgeons National Surgical Quality Improvement Project (ACS NSQIP) database with 30-day follow-up of 2164 patients undergoing elective anterior cervical discectomy and fusion (ACDF). Objective: To determine factors independently associated with increased length of stay (LOS) and complications after ACDF to facilitate preoperative planning and setting of realistic expectations for patients and providers. Summary of Background Data: The effect of individual preoperative factors on LOS and complications has been evaluated in small-scale studies. Large database analysis with multivariate analysis of these variables has not been reported. Methods: The ACS NSQIP database from 2005 to 2010 was queried for patients undergoing ACDF procedures. Preoperative and perioperative variables were collected. Multivariate regression determined significant predictors ( P <0.05) of extended LOS and complications. Results: Average LOS was 2.0±4.0 days (mean±SD) with a range of 0–103 days. By multivariate analysis, age 65 years and above, functional status, transfer from facility, preoperative anemia, and diabetes were the preoperative factors predictive of extended LOS. Major complications, minor complications, and extended surgery time were the perioperative factors associated with increased LOS. The elongating effect of these variables was determined, and ranged from 0.5 to 5.0 days. Seventy-one patients (3.3%) had a total of 92 major complications, including return to operating room (40), venous thrombotic events (13), respiratory (21), cardiac (6), mortality (5), sepsis (4), and organ space infection (3). Multivariate analysis determined ASA score ≥3, preoperative anemia, age 65 years and above, extended surgery time, and male sex to be predictive of major complications (odds ratios ranging between 1.756 and 2.609). No association was found between levels fused and LOS or complications. Conclusion: Extended LOS after ACDF is associated with factors including age, anemia, and diabetes, as well as the development of postoperative complications. One in 33 patients develops a major complication postoperatively, which are associated with an increased LOS of 5 days.